Amnesty, human rights and political transitions : bridging the peace and justice divide - Mallinder, Louise (Studies in international law (Oxford, England), 2008)
Amnesty laws are political tools used since ancient times by states wishing to quell dissent, introduce reforms, or achieve peaceful relationships with their enemies. In recent years, they have become contentious due to a perception that they violate international law, particularly the rights of victims, and contribute to further violence. This view is disputed by political negotiators who often argue that amnesty is a necessary price to pay in order to achieve a stable, peaceful, and equitable system of government. This book aims to investigate whether an amnesty necessarily entails a violati.